Neurophysiological predictors for physical working capacity control: analysis of innovative studies by foreign laboratories in 2010-2016 - Koryagina, J. V.; Nopin, S. V.; Blinov, V. A.; Blinov, O. A. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to make an analytical overview of the most promising studies in athletic neurophysiology and psychophysiology for the period since 2010 performed by the leading foreign university laboratories. The main areas of the studies are: - Sport and brain morphology, - Neurophysiology of sports states, - Ideomotorics and physical working capacity, - Movement control, - Sporting achievements and proprioception.